Selenium Migration Mode in Coal Seams: Insights from Multivariate Analysis, Leaching Investigation, and Modelling - Yao Shan; Yong Qin; Wenfeng Wang (International Journal of Chemical Engineering)
Processes controlling selenium concentrations ([Se]) in mine waters were studied at an operating coalmine district in Xuzhou city, China. The geochemistry and mobility of selenium was studied through leaching experiments, multivariate analysis, and numerical modeling. Results showed that selenium leaching was influenced by selenium occurrence in minerals, pH, electron activity (pe), and sulfur concentration in the water. Selenium occurrence in host rock was mainly sulfide minerals, and clay minerals in coal, respectively. Therefore, the oxidation and dissolution of sulfide minerals and transformation of clays may control the release of selenium. Experimental leaching experiments suggested selenium tends to leach more when the solution has more sulfur dissolved. A positive relationship is established between pH and the amount of Se released into solution with four times more Se released at pH 12 compared to pH 2 when leached with high-purity water. This release behavior is higher in O2-rich environments. The numerical modeling results showed that pH, pe, and sulfur presence in the solution play important roles in selenium adsorption. Selenium was desorbed from adsorbing surfaces under alkaline conditions, specifically when the solution pH was higher than 8. Higher pe values in the solution caused reduced selenium adsorption. In addition, dissolved sulfur competed with selenate for surfaces of adsorption, thus, selenium adsorption decreases as the sulfur concentration increased.